Uso de "ecotécnicas" no manejo de águas pluviais em meio urbano: uma abordagem crítica - Silva, Eduardo Araujo (2010)
The environmental situation of the cities, especially the larger ones, presents serious problems arising from human's inability to meet the demands of the agglomerations as they are settled, generating environments with low conditions of habitability. The supremacy of economic interests on natural ecosystems has established a complex network of impacts in raising resources to build the cities, from the extraction of material to the issuance of its final waste. In the last decades, several issues have been presented, many of them referring to urban systems, however, in spite of all the discussion related to preservation and restoration of ecosystems, there are still few transformations to be seen in the cities. This work aims to identify possible confrontations for this panorama, facing both the needs to meet demands for urban infrastructure and to preserve the environment by broadening the debate about implementation of solutions that comply characteristics and cycles of the territory, as well as increasing environmental quality to conviviality. Emphasis was given to the systems of rainwater management, since its inadequacies or shortcomings have been causing crescent collapses, with catastrophic consequences and severe damage to the affected populations. From reviewing some specific literature to this theme, such as Natural Engineering and Bioengineering of Soils, the concept of Urban Ecotechnique was defined, in which 8 variables have been outlined to analyze the application of 28 building techniques related to rainwater management systems, in order to evaluate the degree of service in qualitative sense. Finally, it has been done a discussion of the results from the interpolation of the information collected in an array, where the 28 techniques were crossed with the 8 variables, in an attempt to synthesize and better illustrate the result of the research process. It was noted that, in addition to the different degrees of service and readings generated, the association in chain of Ecotechniques and the cultural transformation of society can be guiding parameters of new attitudes to overcome the current situation. It was then concluded that the employment of Ecotechniques has been shown as a viable way of allying the resolution of urban environmental issues to the promotion of a cultural transformation that integrates people to the built environment, in a complete and natural way.